2009
DOI: 10.5380/avs.v14i1.13228
|View full text |Cite
|
Sign up to set email alerts
|

Digestibilidade De Uma Dieta Caseira E Dois Alimentos Comerciais, Econômico E Super-Prêmio, Para Cães

Abstract: Foram comparados os coeficientes de digestibilidade aparente (CDA) e a qualidade dasfezes de cães alimentados com uma dieta caseira e dois alimentos comerciais, econômicoe super-prêmio. Seis cães adultos foram distribuídos em delineamento quadrado latinoduplo (3 x 3), com três tratamentos e três períodos, totalizando seis repetições portratamento. As médias foram comparadas pelo teste Tukey. A dieta caseira apresentou osmaiores CDA, não diferindo apenas do CDA do extrato etéreo ácido do alimento superprêmio.O … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
4
0
3
Order By: Relevance
“…On nutrition, it was found that 57.55% (61/106) of the animals receive only dog or cat food, 40.57% (43/106) receive dog or cat food and leftovers of homemade food and 1.89% (2/106) of the animals receive only leftovers of homemade food. Although the homemade diet can be appropriate for the nutritional needs of animals (Félix et al, 2009) it should be noted that nutritional imbalance, perhaps present in the homemade food, can cause dietary deficiencies with deleterious consequences from the point of view of health (Stockman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…On nutrition, it was found that 57.55% (61/106) of the animals receive only dog or cat food, 40.57% (43/106) receive dog or cat food and leftovers of homemade food and 1.89% (2/106) of the animals receive only leftovers of homemade food. Although the homemade diet can be appropriate for the nutritional needs of animals (Félix et al, 2009) it should be noted that nutritional imbalance, perhaps present in the homemade food, can cause dietary deficiencies with deleterious consequences from the point of view of health (Stockman et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the FEDIAF recommendations refer to diets with DM digestibility ≥70% and protein digestibility ≥80%. There are still no published studies investigating the apparent digestibility of nutrients in veterinary diets for the management of canine obesity marketed in Brazil, but these diets are formulated with high‐quality ingredients, and there are studies carried out in Brazil that demonstrated DM digestibility ≥70% and protein digestibility ≥80% in super premium dog foods (Carciofi et al., 2009; Félix et al., 2009). Therefore, it is very likely that the diets analysed in our study have higher digestibility than the values mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…Importante ressaltar que diversos tutores vêm optando apenas por ração como fonte de alimento para seus animais, por ser um alimento completo nutricionalmente (Felix et al, 2009). Percebe-se que a grande maioria dos tutores reconhece a importância da vacinação de seus animais de companhia, atitude está presente nos cuidados básicos para bem-estar animal (Reichmann et al, 2000).…”
Section: Discussionunclassified